A Study of the Impact Resistance of Rubber Concrete at Low Temperatures (−30°C) - Gang Xue; Jia-xiang Liu; Mei-ling Cao (Advances in Civil Engineering)
In the present study, the impact resistance of rubber concrete at low temperatures (−30°C) was examined. The initial and ultimate crack impact times and the ductility indexes were evaluated. This study’s specimens were prepared by adding two different sizes of rubber particles (20 mesh and 50 mesh) in different ratios (0%, 5%, 10%, 15%, and 20%) at both 25°C and −30°C. The concrete specimens were evaluated using a drop hammer weight test method. The results showed that the initial and ultimate crack impact times and ductility indexes of the rubber concrete specimens had decreased at −30°C. Also, the decrease amplitudes were determined to be lower than those of the reference concrete specimens. Consideration was given in this study to the large variations in the impact values, and a two-parameter Weibull distribution method was adopted in order to analyze the obtained experimental data. The results had demonstrated that the impact times of the rubber concrete specimens could be described using the two-parameter Weibull distribution method results.